In search of philosophical foundations for formal ontologies in the digital world: Logical Investigations and realism - Daskalaki, Maria (Neusis, 2024)
The use of digital media for the rapid dissemination and exchange of knowledge and information in the contemporary world brought to the fore a series of philosophical questions pertaining to the representation and the reference of knowledge. The initial underestimation of such questions within the field of computer science led to a practical and theoretical impasse. In an effort to overcome this impasse, “formal ontologies” were introduced. However, despite significant efforts in this field, formal ontologies’ initial aim to facilitate the unification of knowledge representation systems has not been achieved so far. This paper suggests that the investigation of the philosophical foundations of formal ontologies can substantially contribute to the resolution of the difficulties researchers and scientists of this field are confronted with. The elaboration of their fundaments in Husserl’s Logical Investigations, from which they borrow their name, and their interpretation from a realist point of view reveal similarities and common problems between formal ontologies, Husserl and scientific realism. This convergence can form the basis for a fruitful and creative cooperation in the research field of investigating the philosophical presuppositions of formal ontologies.